Advances in the study of fractured reservoirs - Spence, G. H. (Guy H.) (Geological Society special publication, 2014)
Naturally fractured reservoirs constitute a substantial percentage of remaining hydrocarbon resources. Their complex behaviour during production has traditionally proved difficult to predict, causing a large degree of uncertainty in reservoir development. The applied study of naturally fractured reservoirs seeks to constrain this uncertainty by developing new understanding, and is necessarily a broad, integrated, interdisciplinary topic. This book addresses some of the challenges and advances in knowledge, approaches, concepts, and methods.